Pelaksanaan Asimilasi Terhadap Narapidana Wanita di Lembaga Pemasyarakatan Klas Ii B Pekanbaru - Nofri Yansyah; Syaifullah Yophie; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Legally the government already has rules about coaching narapidan, where hukuma given to inmates no longer to retaliation for conduct in doing instead coaching against former prisoners of evil become a good person. Given Undanhg Law Number 12 Year 1995 About Correctional clear direction from the coaching program tujuuan community agencies in conducting development activities, especially in the prison inmate Children Class II B Pekanbaru to be free from punishment as they arrive after the community and be competitive environment within the community. Based on this understanding, the thesis is to formulate three formulation of the problem. namely; First, implementation of Assimilation Against Women in Prison Inmates Children Class II B Pekanbaru, second, Assimilation Implementation Barriers Against Women in Prison Inmates Children Class II B Pekanbaru, Third, efforts are being made to overcome the obstacles in the implementation of Assimilation Against Women in Prison Inmates Children Class II B Pekanbaru.This type of research can be classified in this type of juridical sociological research, because in this study the authors directly conduct research on the location or place under study in order to provide a complete and clear picture of the problems examined. This study was conducted at Children's Penitentiary II Class B Pekanbaru, while the population and the sample is a whole party relating to the issues examined in this study, the data sources used, the data of primary, tertiary and secondary data, the data collection techniques in this study with observations, interviews, questionnaires and literature study.From the research issue, there are three main things that can be inferred First, the implementation of assimilation to inmates can be given to inmates after prisoners undergoing sentence ½. As before granting assimilation given to women prisoners in the form of coaching skills (making crafts, learning salons, learn sewing, etc), and general education development (directed towards the liberation illiterate, blind figures, and blind language). Second, hamabatan encountered in the implementation of assimilation is the lack of socialization, convoluted bureaucracy and infrastructure is less complete. Third, the efforts made to overcome the obstacles in pelasanaan assimilation is to provide socialization of assimilation in the general guidance, information service centers, prisons for women. Advice Author, Implementation assimilation should be given to women prisoners without any request for assimilation, but can be given to female prisoners who are qualified substantive, so that assimilation can be equally given to each inmate.